Shugan Decoction Alleviates Colonic Dysmotility in Female SERT-Knockout Rats by Decreasing M3 Receptor Expression - Wang, Yinshu; Dong, Ying; Wang, Enkang; Meng, Yangyang; Bi, Zijuan; Sun, Shuai; Zhang, Chaochao; Fan, Haiting; Yuan, Jianye (Frontiers in Pharmacology, 2020)
Background: Irritable bowel syndrome (IBS) is a functional gut disease characterized by visceral hypersensitivity and gut motor dysfunction. Serotonin (or named as 5-hydroxytryptamine, 5-HT) is an important neurotransmitter in intestine. High level of 5-HT would accelerate the symptom of IBS. The serotonin reuptake transporter (SERT) is a membrane embedded transporter which has been shown to involve in the pathogenesis of IBS and plays an important role in regulating the 5-HT signal. Aim: We investigated if the gut motor function changed in SERT knockout (SERT KO) rats and if Shugan decoction (SGD) could regulate and by which regulate the intestinal motility in SERT KO rat. Method: SERT KO rat was prepared by TELAN technology. Fecal pellet output was measured for ten consecutive days to estimate distal colonic motility. Small intestinal motility was measured by charcoal meal experiment. The colonic and small intestinal muscle contractile activities were measured by organ bath study. Western blot was used to determine the muscarinic receptor expression in colon tissue. Result: Compared with that in wide type (WT) rats, the defecation amount, the amplitude of spontaneous contraction and the tension of ACh-induced contraction of colonic longitudinal smooth muscle in SERT KO rats were significantly increased.. The expression of muscarinic receptor subtype-3 (M3R) in the colon of SERT KO rats also increased. SGD can relieve the defecation of SERT KO rats. Moreover，SGD reduced the amplitude of spontaneous contraction and the frequency with the tension of ACh-induced contraction of colonic longitudinal smooth muscle and the expression of M3R in colon in SERT KO rats. Conclusions: SERT KO rats show increased defecation companied with enhanced colonic motility and M3R expression in colon. Down-regulating the expression of M3R in the colon maybe involve in the mechanisms of SGD to modify colonic dysmotility and to reduce defecation of SERT KO rats.